Hama Hindū nahīṃ, arathāta, Hindū Musalamāna ādikoṃ se bhinna (Khālisā) - Kānha Siṅgha, 1861-1936 (SAMP early 20th-century Indian books project ;, 1898)
Polemic against the view advanced by the Arya Samaj and others that the Sikhs are Hindus and not a separate religious entity.